Desenvolvimento ontogenético da noção de causalidade - Carneiro, Eliane Gerk Pinto (1984)
This thesis is intended to offer an interpretation for the intersection of Social Psychology and Developmental Psychology in the area of the causality concept development. The current situation of investigation in this field has been critically analysed, in order to encourage new researches as well as the adaptation of teaching and learning methodologies related to empirical knowedge. The text starts with an overview of the philosophical conceptions meant to identify the origins of the different questions that will then he considered by Psychology. The next three chapters present three psychological models for the investigation of causality: the Perceptual Model, the Psychogenetic Model and the Social Model. The empirical evidence obtained in approximately fofty years of research is then assessed in order to evaluate the different directions taken by the principal trends of investigation. The psychogenetic models is finally evaluated in the light of the results obtained in the tests to which its hypotheses were submitted, and further research is suggested so as to integrate the three models that have been presented.